2010
DOI: 10.1016/j.ajo.2010.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of Tissues Compatible with Supernumerary Extraocular Muscles

Abstract: PURPOSE To determine by magnetic resonance imaging (MRI) the prevalence and anatomy of anomalous EOM bands. DESIGN Prospective, observational case series. METHODS High resolution, multi-positional, surface coil orbital MRI was performed using T1 or T2 fast spin echo weighting with target fixation control under a prospective protocol in normal adult subjects and a diverse group of strabismic patients between 1996 and 2009. Images demonstrating anomalous EOM bands were analyzed digitally to evaluate their si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 17 publications
2
27
0
Order By: Relevance
“…Orbital imaging, including high-resolution MRI, have played a special role in deepening the knowledge of the morphology and function of the EOMs and their associated connective tissues [4]. Magnetic resonance imaging of tissues compatible with supernumerary extraocular muscles was studied by Khitri and Demer [7]. These authors provided the largest case series of supernumerary human EOMs identified on high resolution MRI.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Orbital imaging, including high-resolution MRI, have played a special role in deepening the knowledge of the morphology and function of the EOMs and their associated connective tissues [4]. Magnetic resonance imaging of tissues compatible with supernumerary extraocular muscles was studied by Khitri and Demer [7]. These authors provided the largest case series of supernumerary human EOMs identified on high resolution MRI.…”
Section: Discussionmentioning
confidence: 99%
“…These authors provided the largest case series of supernumerary human EOMs identified on high resolution MRI. They assessed incidence of all variants of orbital bands at 0.8% among 118 orthotropic subjects and at 2.4% among 453 patients with strabismus [7]. In the same study, the superior–inferior rectus bands were seen only in 33% of all types of bands detected within the orbit [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations